Effect of Light Intensity on the Abundance of Zooxanthellae on Branching Corals (Acropora sp.) at Pagang Island Waters, West Sumatra - Desnaldi, Muhammad Zikran; Thamrin, Thamrin; Siregar, Sofyan Husein (Journal of Coastal and Ocean Sciences, 2026)
Zooxanthellae are symbiotic microalgae that live within coral tissue, playing a vital role in photosynthesis and providing energy to the coral through their metabolic products. Various environmental factors, including light intensity, can influence the abundance of zooxanthellae in corals. This study aimed to determine the abundance of zooxanthellae in branching corals (Acropora sp.) based on different light intensities and to analyze the effect of light intensity on the abundance of zooxanthellae in branching corals (Acropora sp.). This research was conducted in May 2025 at Pagang Island Waters, West Sumatra. The method used in this research is a field experiment. The coral colonies used in the research were assigned to 4 treatments to achieve different light intensities for the samples. The results of this study indicate that there are differences in the abundance of zooxanthellae in branching corals (Acropora sp.) based on different light intensities. The average abundance of zooxanthellae in treatment 1 (control = 694-702 µE/m2s) was 9,961,707 cells/cm2, in treatment 2 (200 µE/m2s) was 5,715,698 cells/cm2, in treatment 3 (100 µE/m2s) was 3,589,326 cells/cm2, and in treatment 4 (0 µE/m2s) was 1,530,447 cells/cm2. This study also shows a very strong relationship between light intensity and the abundance of zooxanthellae in branching corals (Acropora sp.).